(untitled) (International Journal of Integrative Studies (IJIS), 2026)
Polycystic Ovarian Disease (PCOD) and Polycystic Ovary Syndrome (PCOS) rep-resent profound, multi-systemic endocrinopathies affecting a substantial pro-portion of females of reproductive age globally. While often conflated in general practice, they exist along a spectrum of severity ranging from localized functional ovarian disruptions (PCOD) to widespread metabolic and neuroen-docrine dysfunction (PCOS). The pathophysiology of PCOS is deeply rooted in genetic susceptibility, intrauterine epigenetic programming, and environ-mental modulators-including Endocrine Disrupting Chemicals (EDCs)-that col-lectively induce hypothalamic-pituitary-ovarian (HPO) axis dysregulation and profound peripheral insulin resistance. This comprehensive, highly detailed research report presents an exhaus-tive, evidence-based analysis of the molecular mechanisms driving these syn-dromes. We evaluate the role of hyperinsulinemia as a co-gonadotropin, the complex interplay of adipose tissue dysfunction (altered adipokines), the im-pact of Anti-Müllerian Hormone (AMH) in follicular arrest, and the emerging evidence linking gut microbiome dysbiosis to systemic low-grade inflamma-tion. Furthermore, the interplay between the thyroid axis and ovarian function is critically examined. We provide a rigorous assessment of the contemporary therapeutic land-scape. This includes a detailed analysis of insulin sensitizers (Metformin, spe-cific physiological Myo-Inositol/D-Chiro-Inositol ratios addressing the ”tissue paradox”), selective ovulation induction agents (Letrozole vs. Clomiphene Cit-rate), anti-androgen protocols, and the promising integration of GLP-1 recep-tor agonists for weight management. Surgical interventions, specifically La-paroscopic Ovarian Drilling (LOD), are also objectively evaluated. Utilizing na-tive vector diagrams, we map the intracellular signaling pathways and formu-late a comprehensive, algorithmic clinical decision tree. The primary objective is to provide healthcare practitioners with a robust, objective framework for diagnosing, stratifying, and managing PCOS to mitigate both immediate re-productive concerns and long-term cardiometabolic sequelae.